Genetic analysis of suicide: a sample study in Tuscany (Central Italy) - Martina Focardi; Barbara Gualco; Vilma Pinchi; Norelli Gian-Aristide; Regina Rensi; Elisabetta Pelo; Ilaria Carboni; Ugo Ricci (Oxford University Press, 2022)
Many studies have examined the genetic contribution to suicide. However, data on suicide in the Italian population are scarce. We therefore aimed to address this gap by investigating a cohort of 111 Italians for whom a verdict of suicide had been declared in court in Florence, Italy between 2007 and 2017. This cohort included 86 men and 25 women. DNA samples were obtained from tissues or blood, and 22 genes from multiple neurobiological pathways previously shown to be associated with the pathogenesis of suicide were analysed. Next-generation sequencing was used to compare these gene sequences with those from a large, normal population. In this study, we identified 19 gene variants that were present at significantly lower frequencies in our Italian cohort than in the general population. In addition, four missense mutations were identified in four different genes: Monoamine Oxidase A (MAOA), 5-Hydroxytryptamine Receptor 2 A (HTR2A), Sodium Voltage-Gated Channel Alpha Subunit 8 (SCN8A), and Nitric Oxide Synthase 3 (NOS3). Our study identified several potential genetic links with suicide in a cohort of Italians and supports a relationship between specific genetic variants and suicidal behaviour in this population. Key pointsThis study shows a genetic analysis of suicide.This study examines a cohort of 111 Italians for whom a verdict of suicide had been declared in court in Florence, Italy between 2007 and 2017. DNA samples were obtained from tissues or blood, and 22 genes from multiple neurobiological pathways were investigated.The study supports a relationship between specific genetic variants and suicidal behaviour.